UPAYA PENINGKATAN SIKAP MODERASI BERAGAMA UNTUK ANAK USIA DINI MELALUI MULTIMEDIA INTERAKTIF “KIDS MODERATIONS” DALAM PEMBELAJARAN DI RA MASYITHOH MANGGISAN - Nisak, Farah Fahrun (ICEJ : Islamic Childhood Education Journal, 2022)
The attitude of religious moderation is being promoted by the Indonesian government in the face of thediversity of ideologies and different community backgrounds. The cultivation of attitudes should be carried out from an early age, however, the realization of the cultivation of attitudes of religious moderation in early childhood is still lacking. The aims of the study were (1) to determine the learning of religious moderation in early childhood at RA Masyithoh Manggisan. (2) To find out the implementation of interactive multimedia of religious moderation for early childhood at RA Masyithoh Manggisan. (3) To find out the increase in religious moderation in early childhood through the multimedia “Kids Moderations” in RA. Masyithoh Mangosteen.The type of research used is quantitative research, quasi-experimental research design with one group (one group design pretest posttest). The population in this study were all 19 students in Group B of RA Masyithoh Manggisan. The sampling technique used is simple random sampling with a sample size of 10 students. Data collection  techniques are interviews, observation, and documentation. The research instruments used were observation sheets, interview sheets, pretest sheets and posttest sheets. The data analysis technique used is the analysis prerequisite test, as well as the T test and Gain test.The results showed that 1) the learning of religious moderation at RA Masyithoh had been implemented with habits in the learning environment 2) the implementation of the interactive multimedia game Kids Moderations was carried out in two stages, namely before treatment and after treatment using interactive multimedia Kids Moderations 3) The improvement process the attitude of religious moderation shows the Gain test result of 79%. And there is an increase in the average pretest posttest result of 17.100. So the attitude of religious moderation of early childhood in RA Masyithoh Manggisan increased.